Analysis of Court Decisions Regarding In Persona Claims in Credit Agreement Cases: Analisis Putusan Pengadilan Mengenai Gugatan Kurang Pihak (In Persona) pada Perkara Perjanjian Kredit - Adelya, Eka; Elviandri; Arif Pratama, Rio (Jurnal Media Justitia Nusantara, 2025)
This study examines the legal reasoning employed by judges in resolving civil cases involving insufficient parties (in persona) within credit agreement disputes, and evaluates the consistency of judicial considerations across three levels of the court system: District Court, High Court, and the Supreme Court. The issue arises due to the absence of clear standards regarding which parties must be included in civil lawsuits, particularly in credit agreements that often involve more than two parties. Using a normative juridical method with a statutory and case approach, this research analyzes three decisions: No. 30/Pdt.G/2022/PN WNG, No. 133/PDT/2023/PT SMG, and No. 469 K/Pdt/2024. The findings reveal differing judicial orientations: the District Court prioritizes the substance of default, the High Court emphasizes formal completeness of parties, and the Supreme Court seeks a balance between both. The study concludes that there is no uniformity in judicial assessment concerning party sufficiency in credit agreement disputes, indicating the need for the Supreme Court to issue clear guidelines to ensure legal certainty and the protection of all parties involved.